A wear-resistant heat-insulating coating and its preparation method and application
By combining the surface-modified hollow titanium dioxide microspheres with fluorinated epoxy resin, an wear-resistant heat-insulating coating was prepared, which solved the problem that existing coatings were difficult to reduce thermal conductivity while maintaining high infrared reflectivity, and achieved the improvement of efficient heat insulation and wear-resistant performance.
Patent Information
- Application Number
- CN202411644093.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing thermal insulation coatings are difficult to reduce the thermal conductivity while maintaining high infrared reflectivity, and the uniform dispersion of inorganic fillers and the organic resin are insufficient, which affects the thermal insulation and wear resistance of the coating.
The surface-modified hollow titanium dioxide microspheres are used as filler to prepare wear-resistant heat-resistant coatings with fluorinated epoxy resin. The dispersion technology of a high-speed dispersion machine ensures uniform dispersion of the microspheres, and additives are added to improve the wear resistance of the coating.
It realizes the thermal conductivity of the coating while maintaining high infrared reflectivity, improves the wear resistance and service life of the coating, and significantly improves the thermal insulation and cooling effect of the building facade.
Smart Images

Figure CN119144213B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and in particular to a wear-resistant heat-insulating coating and a preparation method and application thereof. Background Art
[0002] With the substantial increase in energy demand, it is of great significance to achieve building energy conservation by improving the thermal insulation and cooling performance of building facades, reducing energy consumption and emissions. At present, the thermal insulation and cooling of building exterior walls generally adopts the method of coating reflective thermal insulation coatings, which can effectively reduce building energy consumption. Thermal insulation coatings can be divided into radiation type, reflective type and barrier type according to different thermal insulation methods. They are mainly composed of fillers, film-forming substances, solvents, additives, etc., among which fillers play a key functional role.
[0003] However, although infrared reflective coatings alone can reduce the substrate's absorption of infrared rays in sunlight and thus reduce the temperature, the heat conduction between the inside and outside of the substrate can also cause the temperature inside the building to rise. In order to significantly improve the thermal insulation effect of the coating, it is usually necessary to combine infrared reflective coatings with fillers with heat barrier functions, including titanium dioxide or zirconium dioxide with high infrared reflectivity, and hollow glass microspheres or fumed silica with low thermal conductivity as functional fillers. However, the introduction of hollow glass microspheres or fumed silica will weaken the infrared reflection effect of titanium dioxide or zirconium dioxide.
[0004] Therefore, how to reduce the thermal conductivity of the coating while maintaining high infrared reflectivity, and at the same time achieve uniform dispersion of inorganic fillers and their strong interaction with organic resins is the key to preparing high-performance thermal insulation coatings. Summary of the invention
[0005] In response to the above technical problems, the present invention provides a wear-resistant thermal insulation coating and a preparation method and application thereof. Surface-modified titanium dioxide hollow microspheres are used as fillers and are compounded with fluorinated epoxy resin to prepare a high-performance thermal insulation coating, while also improving its wear resistance.
[0006] The present invention protects a wear-resistant heat-insulating coating, which is prepared by mixing an appropriate amount of surface-modified titanium dioxide hollow microspheres, a fluorinated epoxy resin and an additive; specifically, a certain amount of surface-modified titanium dioxide hollow microspheres is added to the fluorinated epoxy resin under vigorous stirring to make the titanium dioxide microspheres evenly dispersed, and then the additives are added to obtain the wear-resistant heat-insulating coating, wherein the additives include a leveling agent, an antioxidant and an anti-ultraviolet aging agent.
[0007] The present invention also protects a method for preparing the above-mentioned wear-resistant heat-insulating coating, comprising:
[0008] Step 1, preparation of hollow titanium dioxide microspheres;
[0009] Step 2, surface modification of titanium dioxide microspheres;
[0010] Step 3, preparation of fluorinated epoxy resin;
[0011] Step 4, high-speed dispersing and mixing to prepare a wear-resistant and heat-insulating coating, wherein the mass ratio of the surface-modified titanium dioxide hollow microspheres to the fluorinated epoxy resin is (15-45):(80-120), and the dispersing time is 0.5-2 h under the condition of a dispersing speed of 4000-7000 rpm in a high-speed disperser.
[0012] Specifically, the specific operations of step 1 are:
[0013] A glucose solution with a concentration of 0.3-0.8 mol / L was added to a high-pressure reactor, and then reacted in a high-temperature oven at 170-200°C for 10-18 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and then dried in a vacuum drying oven. After drying, the product was fully ground to obtain carbon microspheres.
[0014] A certain amount of anhydrous ethanol is added to a high-pressure reactor, and a certain amount of titanium dioxide precursor and the prepared carbon microspheres are slowly added dropwise under stirring, wherein the mass ratio of the titanium dioxide precursor to the ethanol solvent is (3-12):(80-120), followed by a hydrothermal reaction at a reaction temperature of 200-230°C and a reaction time of 18-24 h;
[0015] The obtained product is fully dried and then ground, and finally calcined in a tubular furnace to remove the inner core, and titanium dioxide hollow microspheres are obtained after grinding.
[0016] Specifically, the specific operations of step 2 are:
[0017] The titanium dioxide hollow microspheres are added to a proper amount of a mixed solvent of water and anhydrous ethanol, wherein the mass ratio of water to ethanol in the mixed solvent is (70-95): (3-40), and the mass ratio of the titanium dioxide hollow microspheres to the mixed solvent is (1-3): (10-100);
[0018] After ultrasonic dispersion for 10 to 30 minutes, a silane coupling agent containing an amino functional group is added, and the resulting dispersion is stirred and reacted at a temperature of 30 to 60°C for 6 to 24 hours, wherein the mass ratio of titanium dioxide hollow microspheres to the silane coupling agent is (5 to 30): (0.5 to 2). Finally, titanium dioxide hollow microspheres containing reactive functional groups on the surface are obtained by centrifugation, drying, and grinding.
[0019] The silane coupling agent is preferably a mixture of one or more of γ-aminopropyltriethoxysilane KH-550, γ-mercaptopropyltrimethoxysilane KH-590, and γ-glycidyloxypropyltrimethoxysilane KH-560.
[0020] Specifically, the specific operations of step 3 are:
[0021] Add trifluoroethyl methacrylate TFEMA, bis(carboxymethyl) trithiocarbonate, and azobisisobutyronitrile AIBN into tetrahydrofuran THF solvent, wherein the mass ratio of TFEMA to bis(carboxymethyl) trithiocarbonate is (4-8):(0.5-1.5), and the mass ratio of bis(carboxymethyl) trithiocarbonate to AIBN is (10-40):(0.5-7);
[0022] After dissolving, the mixture was stirred and reacted under nitrogen protection at a temperature of 60-70°C for 12-24 h. After the reaction, the resulting solution was precipitated, washed, and filtered in n-hexane. The product was vacuum dried at 40-90°C for 8-24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), which was recorded as HOOC-PTFEMA-COOH.
[0023] HOOC-PTFEMA-COOH, epichlorohydrin and a catalyst are added to a single-necked flask filled with tetrahydrofuran, stirred at room temperature and then the air in the system is removed, and then heated for reaction under nitrogen protection, wherein the mass ratio of HOOC-PTFEMA-COOH to epichlorohydrin is (5-10):(0.5-2); after the reaction is completed, the mixture is washed with water, and finally water and excess epichlorohydrin are removed by distillation under reduced pressure, and the obtained product is dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin.
[0024] The present invention uses a terminal dicarboxyl fluorine-containing compound to modify the epoxy resin to obtain a novel fluorine-containing epoxy resin, which can better improve the weather resistance and service life of the coating.
[0025] The present invention also protects a heat-insulating coating, which is prepared by adding a curing agent and a diluent into the above-mentioned wear-resistant heat-insulating coating in a certain proportion, stirring the coating evenly, and then coating the coating on the surface of the substrate by roller coating or spraying. After curing, the heat-insulating coating is obtained.
[0026] The present invention is conducive to the use of a silane coupling agent containing an amino functional group to modify the surface of titanium dioxide hollow microspheres as fillers, and to prepare high-performance wear-resistant heat-insulating coatings in combination with fluorinated epoxy resins, which are mainly used on the outer surfaces of buildings and outdoor cabinets to achieve energy-saving and cooling effects. The intrinsic high infrared reflectivity and hollow structure of titanium dioxide are utilized to achieve low thermal conductivity without affecting its infrared reflectivity, reduce the accumulation of heat on the surface of the substrate, and achieve efficient heat insulation and energy-saving effects; in addition, the modification of titanium dioxide hollow microspheres with a silane coupling agent can not only improve the dispersibility of inorganic fillers and improve the compatibility of fillers and fluorinated epoxy resins, but also the active groups on the surface of the fillers can react chemically with fluorinated epoxy resins or curing agents to form covalent bonds, thereby improving the wear resistance and other mechanical properties of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1a Schematic diagram of the synthesis route of dicarboxyl-terminated poly(trifluoroethyl methacrylate);
[0028] Figure 1b Schematic diagram of the synthesis of fluorinated epoxy resin;
[0029] Figure 2 The molecular weight distribution curve of the fluorinated epoxy resin obtained by gel permeation chromatography test;
[0030] Figure 3 This is a graph showing the surface temperature of the thermal insulation coating substrate and the uncoated substrate of Example 5 as a function of time;
[0031] Figure 4 is the thermal gravimetric curve of the modified titanium dioxide hollow microspheres in Example 5;
[0032] Figure 5 This is a schematic diagram of the shell structure of the titanium dioxide hollow microspheres modified with a silane coupling agent and composited with a fluorinated epoxy resin in Example 5 observed under a transmission electron microscope. DETAILED DESCRIPTION
[0033] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The technical scheme of the present invention is described more clearly and completely below in conjunction with specific embodiments and comparative examples. Example 1
[0035] 1. Preparation of hollow titanium dioxide microspheres
[0036] A 0.5 mol / L glucose solution was added to a high-pressure reactor, and then reacted in a high-temperature oven at 180°C for 12 h. After the reaction, it was cooled to room temperature, washed several times with water and ethanol respectively, and finally placed in a vacuum drying oven to dry. After drying, the product was fully ground to obtain carbon microspheres.
[0037] 40 mL of anhydrous ethanol was added to a 100 mL high-pressure reactor, and 2.5 g of tetrabutyl titanate and the carbon microspheres prepared above were slowly added dropwise under stirring; then the reaction was carried out at 200°C for 20 h, the obtained product was fully dried and ground, and finally calcined in a tubular furnace to remove the inner core, and titanium dioxide hollow microspheres were obtained after grinding.
[0038] 2. Surface modification of hollow titanium dioxide microspheres
[0039] 15.0 g of titanium dioxide hollow microspheres were added to a mixed solvent of 100 g of water and 200 g of anhydrous ethanol, and 2.0 g of silane coupling agent KH-590 was added after ultrasonic dispersion for 30 min. The resulting dispersion was stirred and reacted at 40°C for 24 h. Finally, titanium dioxide hollow microspheres with reactive functional groups on the surface were obtained by centrifugation, drying and grinding.
[0040] 3. Preparation of fluorinated epoxy resin
[0041] 10.0 g TFEMA, 2.5 g bis(carboxymethyl) trithiocarbonate and 0.3 g AIBN were added into tetrahydrofuran, dissolved and stirred at 68 °C for 24 h under nitrogen protection. After the reaction, the obtained solution was precipitated, washed and filtered in n-hexane. The product was vacuum dried at 60 °C for 24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), which was recorded as HOOC-PTFEMA-COOH.
[0042] 15.0 g HOOC-PTFEMA-COOH, 2.0 g epichlorohydrin, and sodium hydroxide (catalyst) were added to a single-necked flask filled with tetrahydrofuran, stirred evenly at room temperature, and the air in the system was removed, and then heated under nitrogen protection for reaction. After the reaction was completed, the mixture was washed with water, and finally water and excess epichlorohydrin were removed by vacuum distillation. The obtained product was dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin.
[0043] 4. Preparation of wear-resistant heat-insulating coatings and coatings
[0044] 15.0 g of surface-modified titanium dioxide hollow microspheres were added to 50.0 g of fluorinated epoxy resin under vigorous stirring, and the microspheres were dispersed at 6000 rpm for 1 h using a high-speed disperser, followed by the addition of leveling agents, antioxidants, anti-ultraviolet aging agents and other additives to obtain a wear-resistant heat-insulating coating. Leveling agents, antioxidants, anti-ultraviolet aging agents and other additives are commonly used additives for coatings and will not be elaborated here.
[0045] 10.0 g of diethylenetriamine (curing agent) and 13.0 g of propylene glycol methyl ether acetate (diluent) were added to the above-mentioned wear-resistant thermal insulation coating, and after being stirred evenly, they were coated on the surface of the substrate by roller coating. After curing, the thermal insulation coating was obtained. Example 2
[0046] 1. Preparation of hollow titanium dioxide microspheres
[0047] A 0.6 mol / L glucose solution was added to the autoclave, and then reacted in a high-temperature oven at 190°C for 14 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and finally dried in a vacuum oven. After drying, the product was fully ground to obtain carbon microspheres.
[0048] 40 mL of anhydrous ethanol was added to a 100 mL autoclave, and 2.7 g of tetraethyl titanate and the carbon microspheres prepared above were slowly added dropwise under stirring. The reaction was then carried out at 220°C for 20 h, the obtained product was fully dried and ground, and finally calcined in a tubular furnace to remove the core, and titanium dioxide hollow microspheres were obtained after grinding.
[0049] 2. Surface modification of hollow titanium dioxide microspheres
[0050] 10.0 g of titanium dioxide hollow microspheres were added to a mixed solvent of 30.0 g of water and 120.0 g of anhydrous ethanol, and 2.0 g of silane coupling agent KH-560 was added after ultrasonic dispersion for 20 min. The resulting dispersion was stirred and reacted at 40°C for 18 h. Finally, titanium dioxide hollow microspheres with reactive functional groups on the surface were obtained by centrifugation, drying and grinding.
[0051] 3. Preparation of fluorinated epoxy resin
[0052] 12.0 g TFEMA, 2.0 g bis(carboxymethyl) trithiocarbonate and 0.2 g AIBN were added into tetrahydrofuran, dissolved and stirred at 70 °C for 18 h under nitrogen protection. After the reaction, the obtained solution was precipitated, washed and filtered in n-hexane. The product was vacuum dried at 60 °C for 24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), which was recorded as HOOC-PTFEMA-COOH.
[0053] 15.0 g HOOC-PTFEMA-COOH, 1.7 g epichlorohydrin and sodium hydroxide (catalyst) were added into a single-necked flask filled with tetrahydrofuran, and the air in the system was removed after being stirred evenly at room temperature, and then the system was heated to react under nitrogen protection; after the reaction was completed, the system was washed with water, and finally the water and excess epichlorohydrin were removed by vacuum distillation, and the obtained product was dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin.
[0054] 4. Preparation of wear-resistant heat-insulating coatings and coatings
[0055] 10.0 g of surface-modified titanium dioxide hollow microspheres were added to 50.0 g of fluorinated epoxy resin under vigorous stirring, and the microspheres were dispersed at 7000 rpm using a high-speed disperser for 1.5 h. Subsequently, additives such as leveling agent, antioxidant, and anti-ultraviolet aging agent were added to obtain a wear-resistant and heat-insulating coating.
[0056] 12.0 g of tetraethylenepentamine (curing agent) and 18.0 g of propylene glycol methyl ether acetate (diluent) were added to the wear-resistant thermal insulation coating, stirred evenly, and then coated on the surface of the substrate by roller coating. After curing, the thermal insulation coating was obtained. Example 3
[0057] 1. Preparation of hollow titanium dioxide microspheres
[0058] A 0.3 mol / L glucose solution was added to the autoclave, and then reacted in a high-temperature oven at 170°C for 10 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and finally dried in a vacuum drying oven. After drying, the product was fully ground to obtain carbon microspheres.
[0059] 40 mL of anhydrous ethanol was added to a 100 mL autoclave, and 3.0 g of tetrabutyl titanate and the carbon microspheres prepared above were slowly added dropwise under stirring. The reaction was then carried out at 230 °C for 18 h, the obtained product was fully dried and ground, and finally calcined in a tubular furnace to remove the core, and titanium dioxide hollow microspheres were obtained after grinding.
[0060] 2. Surface modification of hollow titanium dioxide microspheres
[0061] 18.0 g of titanium dioxide hollow microspheres were added to a mixed solvent of 30.0 g of water and 150.0 g of anhydrous ethanol, and 2.2 g of silane coupling agent KH-550 was added after ultrasonic dispersion for 30 min. The resulting dispersion was stirred and reacted at 50°C for 16 h. Finally, titanium dioxide hollow microspheres with reactive functional groups on the surface were obtained by centrifugation, drying and grinding.
[0062] 3. Preparation of fluorinated epoxy resin
[0063] 15.0 g TFEMA, 3.0 g bis(carboxymethyl) trithiocarbonate, and 0.4 g AIBN were added to tetrahydrofuran, dissolved, and stirred at 65°C for 16 h under nitrogen protection. After the reaction, the resulting solution was precipitated, washed, and filtered in n-hexane. The product was vacuum dried at 60°C for 24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), denoted as HOOC-PTFEMA-COOH. The synthetic route is as follows: Figure 1a shown.
[0064] 16.0 g HOOC-PTFEMA-COOH, 2.0 g epichlorohydrin, and sodium hydroxide (catalyst) were added to a single-necked flask filled with tetrahydrofuran, and the air in the system was removed after stirring at room temperature. Then, the system was heated under nitrogen protection for reaction. After the reaction was completed, the system was washed with water, and finally, water and excess epichlorohydrin were removed by vacuum distillation. The obtained product was dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin. The synthetic route is as follows: Figure 1b shown.
[0065] The molecular weight distribution curve of the fluorinated epoxy resin obtained by gel permeation chromatography is as follows: Figure 2 As shown, it can be concluded that the molecular weight of the resin is 10840 g / mol and the molecular weight distribution is 1.39.
[0066] 4. Preparation of wear-resistant heat-insulating coatings and coatings
[0067] 12.0 g of surface-modified titanium dioxide hollow microspheres were added to 40.0 g of fluorinated epoxy resin under vigorous stirring, and the microspheres were dispersed at 6000 rpm using a high-speed disperser for 1 h. Subsequently, additives such as leveling agent, antioxidant, and anti-ultraviolet aging agent were added to obtain a wear-resistant and heat-insulating coating.
[0068] 5.2 g of isophorone diamine (curing agent) and 20.0 g of propylene glycol methyl ether acetate (diluent) were added to the wear-resistant thermal insulation coating, stirred evenly and then coated on the surface of the substrate by spraying. After curing, the thermal insulation coating was obtained. Example 4
[0069] 1. Preparation of hollow titanium dioxide microspheres
[0070] A 0.8 mol / L glucose solution was added to the autoclave, and then reacted in a high-temperature oven at 200°C for 18 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and finally dried in a vacuum drying oven. After drying, the product was fully ground to obtain carbon microspheres.
[0071] 40 mL of anhydrous ethanol was added to a 100 mL autoclave, and 2.8 g of tetraethyl titanate and the carbon microspheres prepared above were slowly added dropwise under stirring. The reaction was then carried out at 200 °C for 21 h, the obtained product was fully dried and ground, and finally calcined in a tubular furnace to remove the core, and titanium dioxide hollow microspheres were obtained after grinding.
[0072] 2. Surface modification of hollow titanium dioxide microspheres
[0073] 20.0 g of titanium dioxide hollow microspheres were added to a mixed solvent of 75.0 g of water and 525.0 g of anhydrous ethanol, and 2.5 g of silane coupling agent KH-550 was added after ultrasonic dispersion for 30 min. The resulting dispersion was stirred and reacted at 60°C for 12 h. Finally, titanium dioxide hollow microspheres with reactive functional groups on the surface were obtained by centrifugation, drying and grinding.
[0074] 3. Preparation of fluorinated epoxy resin
[0075] 13.0 g TFEMA, 2.2 g bis(carboxymethyl) trithiocarbonate and 0.3 g AIBN were added into tetrahydrofuran, dissolved and stirred at 70 °C for 12 h under nitrogen protection. After the reaction, the obtained solution was precipitated, washed and filtered in n-hexane. The product was vacuum dried at 60 °C for 24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), which was recorded as HOOC-PTFEMA-COOH.
[0076] 10.0 g HOOC-PTFEMA-COOH, 1.9 g epichlorohydrin, and sodium hydroxide (catalyst) were added to a single-necked flask filled with tetrahydrofuran, stirred evenly at room temperature, and the air in the system was removed, and then heated under nitrogen protection for reaction. After the reaction was completed, the mixture was washed with water, and finally water and excess epichlorohydrin were removed by vacuum distillation. The obtained product was dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin.
[0077] 4. Preparation of wear-resistant heat-insulating coatings and coatings
[0078] 13.0 g of surface-modified titanium dioxide hollow microspheres were added to 48.0 g of fluorinated epoxy resin under vigorous stirring, and the microspheres were dispersed at 6500 rpm using a high-speed disperser for 1.5 h. Subsequently, additives such as leveling agent, antioxidant, and anti-ultraviolet aging agent were added to obtain a wear-resistant and heat-insulating coating.
[0079] Add 12 g of diethylenetriamine (curing agent) and 19 g of propylene glycol methyl ether acetate (diluent) into the wear-resistant thermal insulation coating, stir evenly and apply it on the surface of the substrate by spraying. After curing, the thermal insulation coating is obtained. Example 5
[0080] 1. Preparation of hollow titanium dioxide microspheres
[0081] A 0.4 mol / L glucose solution was added to the autoclave, and then reacted in a high-temperature oven at 180°C for 15 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and finally dried in a vacuum drying oven. After drying, the product was fully ground to obtain carbon microspheres.
[0082] 40 mL of anhydrous ethanol was added to a 100 mL autoclave, and 2.0 g of tetrabutyl titanate and the carbon microspheres prepared above were slowly added dropwise under stirring. The reaction was then carried out at 210°C for 18 h, the obtained product was fully dried and ground, and finally calcined in a tubular furnace to remove the core, and titanium dioxide hollow microspheres were obtained after grinding.
[0083] 2. Surface modification of hollow titanium dioxide microspheres
[0084] 16.0 g of titanium dioxide hollow microspheres were added to a mixed solvent of 110.0 g of water and 370.0 g of anhydrous ethanol, and 1.4 g of silane coupling agent KH-590 was added after ultrasonic dispersion for 25 min. The resulting dispersion was stirred and reacted at 55°C for 15 h. Finally, titanium dioxide hollow microspheres with reactive functional groups on the surface were obtained by centrifugation, drying and grinding.
[0085] 3. Preparation of fluorinated epoxy resin
[0086] 10.0 g TFEMA, 1.7 g bis(carboxymethyl) trithiocarbonate and 0.23 g AIBN were added into tetrahydrofuran, dissolved and stirred at 65 °C for 15 h under nitrogen protection. After the reaction, the obtained solution was precipitated, washed and filtered in n-hexane. The product was vacuum dried at 60 °C for 24 h to obtain dicarboxyl-terminated poly(trifluoroethyl methacrylate), which was recorded as HOOC-PTFEMA-COOH.
[0087] 10.0 g HOOC-PTFEMA-COOH, 1.9 g epichlorohydrin, and sodium hydroxide (catalyst) were added to a single-necked flask filled with tetrahydrofuran, stirred evenly at room temperature, and the air in the system was removed, and then heated under nitrogen protection for reaction. After the reaction was completed, the mixture was washed with water, and finally water and excess epichlorohydrin were removed by vacuum distillation. The obtained product was dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin.
[0088] 4. Preparation of wear-resistant heat-insulating coatings and coatings
[0089] 12.0 g of surface-modified titanium dioxide hollow microspheres were added to 60.0 g of fluorinated epoxy resin under vigorous stirring, and the microspheres were dispersed at 6500 rpm using a high-speed disperser for 1.5 h. Subsequently, additives such as leveling agent, antioxidant, and anti-ultraviolet aging agent were added to obtain a wear-resistant and heat-insulating coating.
[0090] 7.2 g of m-phenylenediamine (curing agent) and 10.0 g of propylene glycol methyl ether acetate (diluent) were added to the wear-resistant thermal insulation coating, stirred evenly and then coated on the surface of the substrate by spraying. After curing, the thermal insulation coating was obtained.
[0091] 1. Thermal insulation test
[0092] The wear-resistant heat-insulating coatings prepared in Examples 1-5 were coated on the surface of the cabinet, and the performance was compared with that of the cabinet in Comparative Example 1 which was not coated with the heat-insulating coating. The solar reflectivity, near-infrared reflectivity and surface temperature were tested. The results are shown in Table 1.
[0093] Table 1
[0094]
[0095] Under the test of infrared lamp irradiation, the surface temperature of the thermal insulation coating substrate and the uncoated substrate in Example 5 changes with time, as shown in FIG. Figure 3 As shown, it can be seen that after about 12 minutes of infrared light irradiation, the temperature of the two substrates began to stabilize, and after stabilization, the presence of the thermal insulation coating reduced the surface temperature of the substrate by 21°C.
[0096] Titanium dioxide, as a high infrared reflective material, can effectively reduce the absorption of infrared light by the substrate and reduce the accumulation of heat on the surface of the substrate. At the same time, the hollow structure of titanium dioxide can effectively prevent the heat exchange between the external environment and the inside of the coating, reduce heat conduction and achieve thermal barrier properties. This thermal barrier feature of high reflectivity fillers can avoid the influence of different functional fillers on thermal insulation performance and achieve efficient cooling effect. On the one hand, the surface modification of titanium dioxide microspheres can improve its dispersibility in organic resins. On the other hand, it can also achieve covalent bond connection between fillers and fluorinated epoxy resins through the reaction between the functional groups on the surface of the fillers and the functional groups of the resin, thereby improving the interaction between organic and inorganic components and improving the friction resistance and other properties of the coating.
[0097] 2. Wear resistance test
[0098] Comparative Example 2
[0099] In this embodiment, conventional epoxy resin is added, and the remaining steps are the same as those in Embodiment 5.
[0100] Comparative Example 3
[0101] The titanium dioxide microspheres in this example were not surface modified with a silane coupling agent, and the remaining steps were the same as in Example 5.
[0102] The wear resistance of the coatings obtained in Comparative Examples 2 and 3 was compared with that of Examples 3, 4 and 5. 80-grit sandpaper was used for weighted friction, and the number of frictions when the substrate was exposed was observed. The results are shown in Table 2. It can be seen that the modification of the filler and the cross-linking between the filler and the fluorinated epoxy resin or the curing agent significantly improve the wear resistance of the coating.
[0103] Table 2
[0104]
[0105] Figure 4 This is the thermal gravimetric curve of the modified titanium dioxide hollow microspheres in Example 5, from which it can be seen that the mass fraction of the silane coupling agent grafted on the titanium dioxide surface is 6.9%, proving that the titanium dioxide hollow microspheres are successfully grafted with the silane coupling agent.
[0106] The morphology of the titanium dioxide hollow microspheres modified with the silane coupling agent and compounded with the fluorinated epoxy resin in Example 5 was characterized by transmission electron microscopy. Figure 5 As shown, the hollow structure of the microspheres can be clearly observed, and there is an obvious shell structure on the surface of the microspheres, which is the main reason for improving the wear resistance of the coating. The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-mentioned embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a wear-resistant heat-insulating coating, characterized in that: The following steps are involved: Step 1, preparation of hollow titanium dioxide microspheres; Step 2, surface modification of titanium dioxide microspheres; Step 3, preparation of fluorinated epoxy resin, specifically comprising: Add trifluoroethyl methacrylate TFEMA, bis(carboxymethyl) trithiocarbonate, and azobisisobutyronitrile AIBN into tetrahydrofuran THF solvent, wherein the mass ratio of TFEMA to bis(carboxymethyl) trithiocarbonate is (4-8):(0.5-1.5), and the mass ratio of bis(carboxymethyl) trithiocarbonate to AIBN is (10-40):(0.5-7); After dissolving, the mixture was stirred and reacted under nitrogen protection at a temperature of 60-70°C for 12-24 h. After the reaction, the resulting solution was precipitated, washed, and filtered in n-hexane. The product was vacuum dried at 40-90°C. 8-24 h, dicarboxyl-terminated poly(trifluoroethyl methacrylate) was obtained, denoted as HOOC-PTFEMA-COOH; HOOC-PTFEMA-COOH, epichlorohydrin and a catalyst are added to a single-necked flask filled with tetrahydrofuran, and the air in the system is removed after being stirred at room temperature, and then heated for reaction under nitrogen protection, wherein the mass ratio of HOOC-PTFEMA-COOH to epichlorohydrin is (5-10):(0.5-2); after the reaction is completed, the mixture is washed with water, and finally water and excess epichlorohydrin are removed by distillation under reduced pressure, and the resulting product is dissolved in a mixed solvent of butyl acetate and propylene glycol methyl ether acetate to obtain a fluorinated epoxy resin; Step 4, high-speed dispersing and mixing to prepare a wear-resistant and heat-insulating coating, wherein the mass ratio of the surface-modified titanium dioxide hollow microspheres to the fluorinated epoxy resin is (15-45):(80-120), and the dispersing time is 0.5-2 h under the condition of a dispersing speed of 4000-7000 rpm in a high-speed disperser.
2. The method for preparing the wear-resistant heat-insulating coating according to claim 1, characterized in that: Step 1: A glucose solution with a concentration of 0.3-0.8 mol / L was added to a high-pressure reactor, and then reacted in a high-temperature oven at 170-200°C for 10-18 h. After the reaction, it was cooled to room temperature, washed with water and ethanol several times, and then dried in a vacuum drying oven. After drying, the product was fully ground to obtain carbon microspheres. Anhydrous ethanol was added to a high-pressure reactor, and a titanium dioxide precursor and the prepared carbon microspheres were slowly added dropwise under stirring, wherein the mass ratio of the titanium dioxide precursor to the ethanol solvent was (3-12):(80-120), and then a hydrothermal reaction was carried out, the reaction temperature was 200-230°C, and the reaction time was 18-24 h; The obtained product is fully dried and then ground, and finally calcined in a tubular furnace to remove the inner core, and titanium dioxide hollow microspheres are obtained after grinding.
3. The method for preparing the wear-resistant heat-insulating coating according to claim 1, characterized in that: The specific operations of step 2 are: The titanium dioxide hollow microspheres are added to a proper amount of a mixed solvent of water and anhydrous ethanol, wherein the mass ratio of water to ethanol in the mixed solvent is (70-95): (3-40), and the mass ratio of the titanium dioxide hollow microspheres to the mixed solvent is (1-3): (10-100); After ultrasonic dispersion for 10 to 30 minutes, a silane coupling agent containing an amino functional group is added, and the resulting dispersion is stirred and reacted at a temperature of 30 to 60°C for 6 to 24 hours, wherein the mass ratio of titanium dioxide hollow microspheres to the silane coupling agent is (5 to 30): (0.5 to 2). Finally, titanium dioxide hollow microspheres containing reactive functional groups on the surface are obtained by centrifugation, drying, and grinding.
4. The method for preparing the wear-resistant heat-insulating coating according to claim 3, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane KH-550.
5. A thermal insulation coating, characterized in that: Add the curing agent and the diluent into the wear-resistant heat-insulating coating according to claim 1 in proportion, stir evenly, and apply it on the surface of the substrate by roller coating or spraying, and obtain the heat-insulating coating after curing.
6. The thermal insulation coating according to claim 5, characterized in that: The curing agent is a mixture of one or more of diethylenetriamine, tetraethylenepentamine, isophoronediamine and metaphenylenediamine.
7. The thermal insulation coating according to claim 5, characterized in that: The diluent is propylene glycol methyl ether acetate.
8. The thermal insulation coating according to claim 5, characterized in that: The mass ratio of the curing agent to the wear-resistant heat-insulating coating is (5~25):(80~120), and the mass ratio of the diluent to the wear-resistant heat-insulating coating is (15~35):(90~110).
Citation Information
Patent Citations
Flame-retardant membrane material with high mechanical property and preparation method thereof
CN116606469A
Anti-ultraviolet acrylic resin heat insulation coating for building external wall and preparation method thereof
CN117986951A